PENERAPAN MODEL INQUIRY UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA KELAS V SDN SIDOREJO 1 TUBAN - Sumilah Sumilah; Sri Cacik (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2018)
Based on observations in mind that science literacy ability of fifth grade students at SDN Sidorejo 1 Tuban is still low. It is caused by several factors, one of which is a learning process. In the process of learning a lot of students who do not pay attention to the teacher's explanations, the students motivation to learn is still low, and students are not involved in finding a concept. Therefore, the researcher applied the inquiry learning to solve the problem. The purpose of this study was to determine improving student science literacy ability. This research is a Classroom Action Research (CAR) which each cycle consists of four phases: planning, action, observation, and reflection. Instruments used in the study were test sheet of science literacy ability. The data of science literacy ability was analyzed as a percentage. The results showed that after learning by using inquiry learning, the science literacy ability of student increased on all of indicator science literacy ability.